COMPARISON OF PLANNED CAESAREAN SECTIONS PERFORMED AFTER THE LABOR BEGINS WITH THOSE BEFORE THE LABOR BEGINS IN TERMS OF POSTPARTUM BREASTFEEDING AND MATERNAL ATTACHMENT LEVELS - Yilmaz, Ayse Nur; Derya, Yesim Aksoy (Dokuz Eylul Univ Inst Health Sciences, 2022)
Purpose: This study was conducted to compare the postpartum breastfeeding and maternal attachment levels of women who underwent planned caesarean deliveries in which labor had begun and in which it had not. Methods: This comparative-descriptive study was carried in postpartum services of a public hospital and a university hospital in a provincial center in eastern Turkey between March and August of 2017. This study included 180 women who underwent planned caesarean sections after labor began and 180 women who underwent planned caesarean sections before labor began. A personal information form, the LATCH Breastfeeding Assessment Tool, and the Maternal Attachment Scale (MAS) were used to collect the study data. For the statistical evaluation, the percentage distributions, arithmetic means, standard deviations, chi-squared test, independent samples t test, and Pearson correlation analysis results were used. Results: In the puerperant who had undergone planned caesarean sections after labor began, the MAS total score mean was 97.08 +/- 7.54 and the LATCH score mean was 9.34 +/- 1.13. These means were 72.97 +/- 10.20 and 6.96 +/- 1.12, respectively, in the puerperant who had undergone planned caesarean sections before labor began (p<0.001). Additionally, in the puerperant who underwent planned caesarean sections after labor began, it was determined that the rates of breastfeeding and breast milk only feeding were significantly higher, while the jaundice development rate was significantly lower during the first half hour after birth (p<0.05). Conclusion: The postpartum breastfeeding and maternal attachment levels were significantly higher in those women who underwent planned caesarean sections after labor began.
Keywords: After Labor Begins; Before Labor Begins; Maternal Attachment; Planned Caesarean; Postpartum Breastfeeding